Functional Improvement Following Diastasis Rectus Abdominus Repair in an Active Duty Navy Female. Issue 8 (1st August 2016) - Gallus, Katerina M.; Golberg, Kathy F.; Field, Robert
ABSTRACT: Return to physical activity following childbirth can be a difficult process complicated by structural changes during pregnancy. A common problem is the development of a diastasis of the rectus abdominus (DRA), defined as a horizontal separation of the abdominus muscles at the linea alba. Recent data indicate that the greater the distance of separation of the muscle, the worse the functional ability. We describe a 24-year-old active duty U.S. Navy female G1P2 with a diagnosis of DRA. At 2 months postpartum, she was referred to physical therapy because of back pain and inability to meet baseline activities of daily living. After 4 months of physical therapy, she was unable to complete curl ups as required by U.S. Navy physical fitness standards. Abdominoplasty with imbrication of the abdominal wall diastasis was performed followed by additional physical therapy, after which she returned to baseline functioning. The restoration of functional ability postoperatively suggests there is a therapeutic indication for surgical correction of DRA. In high-functioning military patients with DRA who fail to return to baseline level of activity following a trial of physical therapy, surgical intervention should be considered to obtain the optimal functional ability.